Life System Modeling and Intelligent Computing International Conference on Life System Modeling and Simulation, LSMS 2010, and International Conference on Intelligent Computing for Sustainable Energy and Environment, ICSEE 2010, Wuxi, China, September 17-20, 2010. Proceedings, Part I - Li, Kang.; Li, Xin.; Ma, Shiwei; Irwin, George W.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the International Conference on Life System Modeling and Simulation, LSMS 2010, and International Conference on Intelligent Computing for Sustainable Energy and Environment, ICSEE 2010, held in Wuxi, China, in September 2010. The papers are organized in topical sections on intelligent modeling, monitoring, and control of complex nonlinear systems; modeling and simulation of societies and collective behaviour; advanced theory and methodology in fuzzy systems and soft computing; biomedical signal processing, imaging, and visualization; computational intelligence in utilization of clean and renewable energy resources; innovative education for sustainable energy and environment; and intelligent methods in power and energy infrastructure development.
The First Section: Intelligent Modeling, Monitoring, and Control of Complex Nonlinear Systems -- Research on Steam Generator Water Level Control System Based on Nuclear Power Plant Simulator -- Stabilization for Networked Control Systems with Packet Dropout Based on Average Dwell Time Method -- Modeling of Real-Time Double Loops System in Predicting Sintering$1 (Bs BTP -- An Orthogonal Curvature Fiber Bragg Grating Sensor Array for Shape Reconstruction -- Implementation of the PCB Pattern Matching System to Detect Defects -- A New Technique of Camera Calibration Based on X-Target -- Application Research of the Wavelet Analysis in Ship Pipeline Leakage Detecting -- Analysis and Implementation of FULMS Algorithm Based Active Vibration Control System -- Performance Analysis of Industrial Wireless Network Based on IEEE 802.15.4a -- A Hybrid Ant Colony Optimization and Its Application to Vehicle Routing Problem with Time Windows -- Modeling and Simulation of a Yacht Propulsion System -- The Second Section: Modeling and Simulation of Societies and Collective Behaviour -- Two-Phase Clock Auction Design -- Research on Simulation of Multi-agents Competition Model with Negotiation -- Synchronization of Ghostburster Neurons under External Electrical Stimulation: An Adaptive Approach -- The Third Section: Advanced Theory and Methodology in Fuzzy Systems and Soft Computing -- A Collision Detection System for an Assistive Robotic Manipulator -- Adaptive Visual Servoing with Imperfect Camera and Robot Parameters -- An Interactive Method to Solve the Priorities of Attributes While the Preferences of Evaluated Units Are under Considering -- Solving Delay Differential Equations with Homotopy Analysis Method -- The Fourth Section: Biomedical Signal Processing, Imaging, and Visualization -- EEG Classification Based on Artificial Neural Network in Brain Computer Interface -- Open Electrical Impedance Tomography: Computer Simulation and System Realization -- Digital Watermarking Algorithm Based on Image Fusion -- The Dynamics of Quorum Sensing Mediated by Small RNAs in Vibrio Harveyi -- An Algorithm for Reconstruction of Surface from Parallel Contours and Its Section Contour Extraction in any Cutting Plane -- Simulation Modeling of Network Intrusion Detection Based on Artificial Immune System -- The Fifth Section: Computational Intelligence in Utilization of Clean and Renewable Energy Resources -- Organic Acid Prediction in Biogas Plants Using UV/vis Spectroscopic Online-Measurements -- Power Quality Disturbances Events Recognition Based on S-Transform and Probabilistic Neural Network -- A Coordinated Heat and Electricity Dispatching Model for Microgrid Operation via PSO -- MPPT Strategy of PV System Based on Adaptive Fuzzy PID Algorithm -- The Sixth Section: Innovative Education for Sustainable Energy and Environment -- Optimized Approach to Architecture Thermal Comfort in Hot Summer and Warm Winter Zone -- The Application of Computational Fluid Dynamics (CFD) in HVAC Education -- The Seventh Section: Intelligent Methods in Power and Energy Infrastructure Development -- Power-Aware Replacement Algorithm to Deliver Dynamic Mobile Contents -- Study on High-Frequency Digitally Controlled Boost Converter.s
Keywords: Computer science; Computer software; Data mining; Information storage and retrieval systems; Computer simulation; Biometrics; Bioinformatics; Computer Science; Computational Biology/Bioinformatics.; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Biometrics; Algorithm Analysis and Problem Complexity; Simulation and Modeling